Immune responses to Cowdria ruminantium infections - Totte, P.; Bensaid, A.; Mahan, S.M.; Martínez, D.; McKeever, Declan J. (Elsevier, 1999)
Understanding the basis of protective immunity to Cowdria ruminantium will facilitate the development of an effective subunit vaccine against heartwater in ruminants and contribute to a better definition of protective immune mechanisms to obligate intracellular pathogens in general. Until recently, immunological studies of heartwater in ruminants concentrated solely on antibody responses. Since 1995, the mechanisms underlying cell-mediated immunity of heartwater have been analysed. Progress achieved in these areas is discussed here by Philippe Totte and colleagues, with special emphasis on ruminants, the natural hosts of C. ruminantium.